Applications of Underwater Acoustics in Polar Environments - Gavrilov, Alexander; Mikhalevsky, P. (Elsevier, 2017)
The unique feature of the Arctic and Antarctic polar oceans that affects underwater acoustics, both the propagation of sound and the ambient noise, is the presence of sea ice that seasonally expands and retreats and ice shelves extending from the land into the ocean. They also have important differences. In the last two decades there has been a significant reduction of both the extent and thickness of the ice in the Arctic while there has been an increase in the extent of the sea ice in the Antarctic. The Arctic Ocean is a Mediterranean basin with limited communication to the world’s oceans while the Southern Ocean surrounds the continent of Antarctica and is contiguous with the south Atlantic, south Pacific, and Indian Oceans and acoustically linked to the deep sound channel of the world’s oceans.